A concept of virtuous administrator and the dilemma of public officials - Awang, Saadon (2020)
One of the main responsibilities of a public official is to serve the public interest. Basically, public interest can be divided into several responsibilities such as public property, public money, public safety and public health. All those responsibilities should be well protected by public officials in order to ensure the wellness and well beings of the people. Wellness and well beings of the people can only be achieved by the qualities of public officials with highly integrity and transparency in carrying out their duties. Public official with highly integrity and transparency is required to serve the duties known with the concept of virtuous administrator. Today, issues of unethical behaviors involving public officials have become global issues. These are due to the lack of integrity and transparency among public officials, which is referred as their failure to carry out their duties, hence, their role as virtuous administrator in concept. This paper discusses about the concept of virtuous administrator, required qualities public officials should have, and measures used to ensure the fulfillment of their duties referred as virtuous administrator.